Quantification of within patient Staphylococcus aureus phenotypic heterogeneity as a proxy for presence of persisters across clinical presentations - Baer, Julian (University of Dundee, 2022)
Staphylococcus aureus was isolated from patients suffering cardiovascular, prosthetic joint or other infections and plated on Columbia sheep blood agar. Macroscopic time-lapse imaging was performed to quantify colony appearance-time and growth-rate. As a baseline reference, the same time-lapse imaging protocol was used after subculturing clinical isolates in tryptic soy broth until bacteria reached exponential growth phase.
Experiment Description
After Experiment A or B, bacteria were stored at -80C. Bacteria were restreaked on columbia sheep blood agar and single colonies inoculated in tryptic soy broth for overnight growth. These cultures were dilute 1:10 and incubated for 2h. From these exponential cultures, time-lapse imaging was started.
Keywords: FOS: Biological sciences; FOS: Biological sciences